Modelling aerosol optical properties over urban environment (New Delhi) constrained with balloon observation. (15th May 2019) - Ahlawat, A.; Mishra, S.K.; Goel, V.; Sharma, C.; Singh, B.P.; Wiedensohler, A.
Abstract: Vertical variation in aerosol optical properties [e.g. Single Scattering Albedo (SSA) and aerosol extinction coefficient] over a polluted environment is extremely important for better understanding of columnar radiative characteristics. The present case study over a typical polluted environment (New Delhi) discusses the vertical profile (ground to 700 m) of modelled optical properties of atmospheric particles at different altitudes. Here, we used the aerosol physico-chemical data generated in the tethered balloon-based observation conducted at CSIR-NPL, New Delhi (28° 38′ 10″ N, 77° 10′ 17″ E) from 21st −27th February 2014. Based on the microscopic observations of individual particles, we developed the aerosol model shapes (coated spheres) for simulating their optical properties. Total three cases were considered for simulating the aerosol optics at varying altitude; Case A: External mixture of coated dust and coated sulfate particles; Case B: External mixture of coated dust, coated sulfate, coated OC (Organic Carbon) and coated EC (Elemental Carbon) (with assumption that 6% EC at ground level); Case C: External mixture of coated dust, coated sulfate, coated OC and coated EC (with assumption that 10% EC at ground level). At 550 nm wavelength, the value of SSA has been found to be highest (i.e. 0.985) at 200 m altitude for Case A while Case B (i.e. 0.9523) and Case C (i.e. 0.9291) show highest values at 500 m altitude. SSA was found to be maximum at 500 m altitude for both Case B and Case C due to the presence of lowest graphitic counts at that particular altitude. Case B and Case C exhibit similar pattern but differ in magnitude, this is due to two EC extremities at ground level i.e. minima (6%) and maxima (10%). The percentage deviation in SSA from ground level to 700 m was found to be highest for Case C (i.e. 5.95%) followed by Case B (i.e. 4.19%) and Case A (i.e. 1.4%). Modelled aerosol optical properties within boundary layer may improve our understanding about the thermodynamics of lower atmosphere. Highlights: A case study over a typical polluted environment (New Delhi) discusses the vertical profile of modelled optical properties of atmospheric particles at different altitudes. The aerosol physico-chemical data (bulk and individual particle level) used to simulate the vertical profile of aerosol optical properties. Better assessment of vertical profile of aerosol optical properties plays an important role in reducing the uncertainties associated with radiative forcing. Frequent airborne observations will certainly provide statistically significant region-specific aerosol properties.